The asterceae as natural coagulants of the water from the bogotá river (Upper basin) (2016)
At the present time, aluminum sulfate (Al2 (SO4 )3(s)) is used as a traditional coagulant. In the developing countries, supplies of it are short, thus, there is a need for an alternative, taking into account the diversity of promising native plants they may be used as a source. One such source are the Asteraceae, a family which has more than 23,500 species distributed among 1600 genera, which means that they are the family of Angiosperms with the greatest biological wealth and diversity. The effectiveness as coagulants of extracts with a medium-high polarity of species of the Asteraceae family in the waters from the upper basin of the Bogota river were evaluated. To do that, the optical density at 500 nm (DO50) of a suspension of turbid water from the Bogotá river (upper basin) was measured, with variable volumes of the extracts obtained from the Asteraceae family. The species from the waters of the Bogotá river which showed the greatest coagulant capacity, at 50 ppm, are: Chromolaena perglabra (57.1%), Achyrocline vell. aff. bogotensis (43.4), Chromolaena odorata (41.1%) and Chromolaena bullata (39.8%), with respect to the aluminum sulfate, (72.7%), zinc sulfate (43.3%) and ammonium chloride (45.5%). At 100 ppm the coagulant capacities were: Chromolaena perglabra (41.1%) and Lourtegia stoechadifolia (32.3%), with respect to the aluminum sulfate (83.6%), zinc sulfate (55.0%) and ammonium chloride (66.7%); and at 250 ppm Lourtegia stoechadifolia (26.2%), with respect to the aluminum sulfate (87.5%), zinc sulfate (64.9%) and ammonium chloride (83.3%). Those results show that the extracts of the species under study, when subjected to this electroscropic technique, have a smaller coagulant capacity at a higher concentration, in contrast with the case of aluminum sulfate, zinc sulfate and ammonium chloride. The Chromolaena perglabra, Achyrocline vell. aff. bogotensis and Chromolaena odorata species show the greatest coagulant capacity with respect to the zinc sulfate and are very close to that of aluminum sulfate and ammoniumchloride.